Furrows in the southeastern Scan Basin, Antarctica: interplay between tectonic and oceanographic influences - Lobo, F.J.; Hernández-Molina, Francisco Javier; Bohoyo, F.; Galindo-Zaldívar, Jesús; Maldonado, Antonio; Martos, Y.M.; Rodríguez-Fernández, J.; Somoza-Losada, Luis; Vázquez, Juan Tomás (Geo-Marine Letters, 2011)
Multibeam echosounder data and TOPAS seismic reflection profiles collected during the AntPac 1997, Scan 2004, and Scan 2008 cruises aboard the RV Hespérides reveal a host of surficial geomorphological features as yet poorly investigated in the Scan Basin, south-central Scotia Sea. This area represents one of the deep gateways between the Weddell Sea and the Scotia Sea, since it enables the northward flow of a branch of the Weddell Sea Deep Water (WSDW). Analysis of the data identifies numerous elongated depressions interpreted as furrows in the southernmost sector of the basin. These furrows show two main trends, i.e., either N–NNW parallel to, or NE oblique to regional bathymetric contours. These trends plausibly reflect a tectonic influence on the bottom-flow distribution, conditioned by a set of recent, conjugate strike-slip faults that developed on the seafloor under dominant NNE–SSW compression and orthogonal extension. The furrows exhibit distinct geomorphological patterns at either side of the basin, which can be related to west–east asymmetry in the WSDW flow direction. Consistent with existing knowledge of regional WSDW dynamics, northward WSDW overflows would be channeled along the western part of the basin at higher bottom-current velocities, thereby generating more erosional-type furrows that are straighter, more elongated, and have more abrupt sidewalls than their eastern counterparts. In contrast, weaker southward WSDW would flow along the eastern part of the basin, resulting in more depositional-type furrows that are more curved, less elongated, and have gentler sidewalls. Sí